Mandy Brown: capstone - Brown, Mandy, artist (Colorado State University. Libraries, 2014)
The artist's statement: As a graphic artist, I am very interested in eye-catching designs with the use of my own hand-rendered font to draw in the viewer. I started my college career in Equine Science and Civil Engineering but graduated with a double major in Graphic Design and Marketing. I have been able to merge all these topics into my designing process. I love taking the emotions and feelings from words or phrases and being able to come up with a structured typographic design that depicts the emotion. There is a lot of power in words, and being able to manipulate the letters to have them take on their own personality is a passion of mine. I have been able to get a lot of inspiration for my designs though music and being outdoors. I am a country girl at heart and most of my personal designs reflect it. I am inspired by southern/country styles and I am always trying to manipulate them to be more modern. For business designs and other non-personal projects, I find inspiration by submerging myself in the company, or theme itself. I still try to incorporate my own typography to add a small touch of myself into the process. I find that adding your own personal touch to projects gives it the little push to make it unique and stand out. Hand-rendered type can get busy within its self, so I have found that keeping everything simple is important. My best designs are simple and to the point. While creating typography is important to me, I am also a fan of painting and oil pastels. Lately, I have been trying to incorporate the two mediums into my design process. The different textures and images you can get from incorporating different mediums into graphic design can push the final design to the next level. There are endless possibilities when it comes to incorporating the fine arts into the computer design process and I am interested in finding out how to incorporate the two for a successful finished product. Having a marketing background has also been an advantage for me while designing for companies. I have the business knowledge, and understand the basic idea of what they are looking for in logos, advertisements, and posters. The business side is interested in copy and wants to draw in the viewer though catch phrases and promotions. But being able to show them how a simple artistic design can be more successful is a great feeling. Each process, weather a personal design or not, has a long process. It all starts with an inspiration from day to day life or from research. Then sketching, and sketching, and more sketching, until I get an idea or image I am happy with. There is never a moment when my first sketch is the design I use. Modifications, color changes, and adjustments are made over and over again until I am finally satisfied with the final product.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.